Adaptive procedure for camber control of forward cantilever structures - Santos,M. F. L. O. (2016)
ABSTRACT In forward cantilever structures, segments are built from previous ones, therefore construction loads must be carried by the partly completed structure. As the cantilever is moved forward deformations increase and corrections must be made during the construction phase. In camber control, corrective displacements are applied to compensate for deformations. The proposed procedure assimilates topographical survey data collected at each construction stage to update the structural model by minimizing the differences between real and computed displacements. Concrete material properties are used as design variables in an optimization process that drives them to values that better represent the material actually used in construction. This is an iterative process where new data are assimilated at each new structural deformed configuration. New camber values are computed and applied to segments that will be cast in the future in order to reach the desired final design profile. The use of the procedure leads to residual displacements of no greater than 5% of the total deformation without camber.